1998
DOI: 10.1182/blood.v92.10.3730.422k20_3730_3736
|View full text |Cite
|
Sign up to set email alerts
|

Immunostimulatory CpG Oligodeoxynucleotides Enhance the Immune Response to Vaccine Strategies Involving Granulocyte-Macrophage Colony-Stimulating Factor

Abstract: Immunostimulatory oligodeoxynucleotides containing the CpG motif (CpG ODN) can activate various immune cell subsets and induce production of a number of cytokines. Prior studies have demonstrated that both CpG ODN and granulocyte-macrophage colony-stimulating factor (GM-CSF) can serve as potent vaccine adjuvants. We used the 38C13 murine lymphoma system to evaluate the immune response to a combination of these two adjuvants. Immunization using antigen, CpG ODN, and soluble GM-CSF enhanced production of antigen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…In support of this additional possibility, it should be noted that GM-CSF, a cytokine with adjuvant activity, also induces the survival and proliferation of cells of the monocyte/macrophage lineage, including BMDM [30]. GM-CSF is produced at sites of immune and inflammatory reactions and the synergistic proliferative response reported above between the active adjuvants and GM-CSF may have some in vivo significance, particularly because GM-CSF and other adjuvants appear to demonstrate synergy in potentiating immune reactions in vivo [29]. As mentioned, the synergistic proliferative effect with low doses of CSF-1 could also be significant because monocytes/macrophages in vivo are likely to be exposed continuously to such low doses in several tissues [10][11][12].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In support of this additional possibility, it should be noted that GM-CSF, a cytokine with adjuvant activity, also induces the survival and proliferation of cells of the monocyte/macrophage lineage, including BMDM [30]. GM-CSF is produced at sites of immune and inflammatory reactions and the synergistic proliferative response reported above between the active adjuvants and GM-CSF may have some in vivo significance, particularly because GM-CSF and other adjuvants appear to demonstrate synergy in potentiating immune reactions in vivo [29]. As mentioned, the synergistic proliferative effect with low doses of CSF-1 could also be significant because monocytes/macrophages in vivo are likely to be exposed continuously to such low doses in several tissues [10][11][12].…”
Section: Discussionmentioning
confidence: 98%
“…Monocyte-macrophage lineage cells may be exposed to GM-CSF at sites of inflammation or immune reactions [27,28]; also GM-CSF and other adjuvants can show synergy in the potentiation of immune responses [29]. We had previously reported that oxLDL can synergize with GM-CSF for BMDM DNA synthesis even at optimal GM-CSF concentrations [13].…”
Section: Synergy With Gm-csf and Csf-1 For Adjuvant-induced Bmdm Prolmentioning
confidence: 99%
“…The difference in CTL activity, however, was not as striking as core-speci®c antibody, which might be due the secreted nature of the fusion protein by expression vector in the study. Reports from other studies are still controversial, some showing that GM-CSF can activate both Th1 and Th2 immune responses whereas others report that GM-CSF stimulates only either Th1 or Th2 response [Okada et al, 1997;Liu et al, 1998;Sin et al, 1998;Stamp¯i et al, 1998]. The balance of activation of DC1 or DC2 by GM-CSF plasmid DNA injection might be one of the factors to result in these Th1 and Th2 responses [Pulendran et al, 1999;Rissoan et al, 1999].…”
Section: Discussionmentioning
confidence: 99%
“…antibody-forming cells by adult and neonatal splenocytes. 21 In vivo, CpG-ODN are shown here to essentially enhance adult IgG2a responses to TNP-Ficoll, similar to their in¯uence on IgG2a responses to protein vaccines 22,23 and model protein antigens. 24±27 This`T helper type 1 driving' immunomodulatory property of CpG-ODN has been largely associated with their capacity to enhance IL-12 production by APC, 28 which suggests that TNP-Ficoll responses may be in¯uenced by APC activation.…”
Section: Discussionmentioning
confidence: 99%